RELEVANCE OF MAHATMA GANDHI’S SOCIAL AND POLITICAL THOUGHTS: A PHILOSOPHICAL STUDY - Patil, Manoj Uttamrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mohandas Karamchand Gandhi alias Mahatma Gandhi was a great figure in the field of non-violence, peace and humanitarianism. He played a significant role in the peace and freedom movement. He put forward many ideas related to socio-political change. Gandhiji’s thoughts are basically philosophical. Because he was inspired by various great thinkers of the world. Mahatma Gandhi put forward many social, political, educational and economic concepts to bring about positive changes in the society. By studying his thoughts, we imbibe new ideas. Undoubtedly, Gandhiji was a social engineer. Who tried to create a new human society where everyone could live in peace. In terms of social change, Gandhi always tried to establish a welfare state (Ram Rajya) through the path of truth and non-violence. Sarvodaya means the welfare of all / the rise of all. The welfare of all was his ultimate dream. According to him, we cannot achieve anything through violence. Because violence destroys both ourselves and the enemy; but non-violence is always beneficial to both. Truth and non-violence help us purify our soul. Mahatma Gandhiji always tried to bring about change in society through non-violent and peaceful means, Gandhiji made a great contribution to making the society understand the power of the virtues of truth, non-violence, love and equality of all religions. An attempt will be made through this research work to understand the relevance of various socio-political principles and philosophies of Mahatma Gandhiji.